2015
DOI: 10.1111/eip.12289
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐cognitive skills training enhances computerized cognitive remediation outcomes among individuals with first‐episode psychosis

Abstract: MST may be an important component within cognitive remediation programmes for first-episode psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Central to this is cognitive remediation, an intervention grounded in understanding the mechanisms of behaviour with a goal of improving functioning (Breitborde et al, 2017). It aims to enhance cognitive skills, such as sustained attention, to modify behaviour (Virk, Williams, Brunsdon, Suh and Morrow, 2015) and has demonstrated to be successful among disorders with similar cognitive abnormalities to psychopathy (e.g.…”
Section: How Effective Is Existing Psychological Treatment For Psychomentioning
confidence: 99%
“…Central to this is cognitive remediation, an intervention grounded in understanding the mechanisms of behaviour with a goal of improving functioning (Breitborde et al, 2017). It aims to enhance cognitive skills, such as sustained attention, to modify behaviour (Virk, Williams, Brunsdon, Suh and Morrow, 2015) and has demonstrated to be successful among disorders with similar cognitive abnormalities to psychopathy (e.g.…”
Section: How Effective Is Existing Psychological Treatment For Psychomentioning
confidence: 99%
“…For the current study, participants will complete two, one-hour cognitive remediation sessions per week for 6 months (i.e., 26 weeks; 52 visits). In a previous study of MCR among individuals with first-episode psychosis (Breitborde et al 2014 ), we found that individuals who received this dosage of MCR experienced greater cognitive and functional improvements (e.g., increased educational/occupational functioning) than individuals who completed only the PSSCogRehab computer activities (i.e., no metacognitive discussion).…”
Section: Methodsmentioning
confidence: 59%
“…For the current study, we will provide participants metacognitive remediation (MCR: (Breitborde et al 2014 )). As part of MCR, participants complete computerized cognitive training activities that are included in the program PSSCogRehab (Bracy 1995 )--a computerized cognitive training program frequently used in past studies of cognitive remediation in serious mental illness (Kurtz et al 2007 ; Greig et al 2007 ; Bell et al 2001 ; Fiszdon et al 2004 ; Fiszdon et al 2005 ; Fiszdon et al 2006 ; Hogarty et al 2004 ; Eack et al 2009 ; Eack et al 2007 ; Breitborde et al 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting step-based care model inspired by these data is displayed in figure 1. The psychotherapy track was influenced by the step-based model of psychotherapy proposed by Nelson et al 20 and ranges from (i) brief psychoeducation on the clinical high-risk phase and substance use reduction programme to (ii) the unified protocol (ie, a transdiagnostic CBT protocol developed by Barlow et al 46 to address emotional disorders such as anxiety and depression) to (iii) targeted psychotherapies designed specifically to address attenuated psychotic symptoms (CBT CHR ) and functional difficulties and cognitive deficits (metacognitive remediation therapy) 47…”
Section: Methods and Analysismentioning
confidence: 99%